2014
DOI: 10.1044/2014_jslhr-h-13-0138
|View full text |Cite
|
Sign up to set email alerts
|

Validating Models of Clinical Word Recognition Tests for Spanish/English Bilinguals

Abstract: Shi and Sánchez's (2010) models incorporating key linguistic variables (AOAE, LD, and average/relative proficiency ratings) can help clinicians predict bilingual clients' relative success in word recognition in Spanish versus English. These models are appropriate for current clinical work with S/E bilinguals in metropolitan areas similar to New York City.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…It is difficult to create non–English-specific word lists because it requires extensive development and validation (22). In addition, in 2019, only 8% of audiologists reported they were bilingual (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to create non–English-specific word lists because it requires extensive development and validation (22). In addition, in 2019, only 8% of audiologists reported they were bilingual (23).…”
Section: Discussionmentioning
confidence: 99%
“…We recommend increased referral to CIE in patients who do not speak English as their primary language with PTA greater than 60 dB. It is difficult to create non-English-specific word lists because it requires extensive development and validation (22). In addition, in 2019, only 8% of audiologists reported they were bilingual (23).…”
Section: Discussionmentioning
confidence: 99%
“…Across university settings, there is often a large population of nonnative speakers of English, including nonnative bilinguals who reside in the United States, as well as international students attending school in the United States. Recent census data reported that 55 million individuals speak a language other than English at home (cited by Shi, 2014). According to the US Census Bureau, by 2060, approximately one in five of the population in the United States is projected to be foreign born (Colby and Ortman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, monolingual and bilingual speakers of English tend to differ along a range of dimensions that could affect masked speech recognition, including linguistic knowledge and access to educational resources (Calvo & Bialystok, 2014;Schneider, Martinez, & Owens, 2006). One of the most studied factors is the age at which the test language was acquired (Meador et al, 2000;Neave-DiToro, Rubinstein, & Neuman, 2017;Shi, 2010Shi, , 2014Weiss & Dempsey, 2008). Late bilinguals perform more poorly than early bilinguals (e.g., Mayo et al, 1997), and age of acquisition covaries with many of the other predictors of language proficiency (Flege, 2019).…”
mentioning
confidence: 99%